Masyarakat Kota, Gereja dan Persoalan Sampah: Suatu Tinjauan Teologis terhadap Tata Ruang dan Kelestarian Ekologi Kota di Kelurahan Naikoten I, Kota Kupang - Esry Wahyuni Beama; Rolin Ferdilianto Sandelgus Taneo (Unit Penerbitan Informasi dan Teknologi Sekolah Tinggi Teologi Gereja Kalimantan Evangelis (STT GKE), 2026)
The waste problem is a serious issue facing urban communities. Furthermore, it also contributes to the deterioration of urban planning. This is truly an ecological issue. Addressing it requires the involvement of all parties, including the church. Therefore, the call to care for nature is an application of living faith. Furthermore, caring for nature becomes a faith-based awareness that nature is also a fellow creation of God. This framework of understanding demonstrates the construction of Christian faith that sides with nature. Therefore, this paper examines not only the reality of urban waste but also how Christian theology contributes to efforts to address it. To complete this paper, we used a literature studies methods, to sharpen the analysis of the issues raised. The hope behind this paper is to raise awareness among the public, the church, and all related elements within it, in raising awareness of environmental care. Urban Spatial Planning and the planned Trust Free Day (TFD) program, developed from Car Free Day (CFD), are also proposed in this paper.